ANTISOCIAL DISORDER OF JOKER CHARACTER IN THE DARK KNIGHT MOVIE DIRECTED BY CHRISTOPHER NOLAN - Aprillia Aprillia; Endang Sri Andayani; Chodidjah Chodidjah; Khoirunnisa Khoirunnisa (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2020)
The objective of this research is to know what is antisocial disorder that was conducted by watching the dark knight movie. In this paper, the writers used descriptive qualitative method by visited the library and browsed of internet to get the references and data that related to the topic. For data collection, all information was collected by librarian research to obtain the theories of literary work and all support information that related to the objective of the research. The next stage was analyzing of The Dark Knight movie by watching it several times . The result of this research indicated that; (1) there are seven symptopms of antisocial disorder that occurred in joker character such as failure to conform to social norm, deceitfulness, impulsivity, irritability and aggressiveness, reckless disregard for safety of self or others, consistent irresponsibility, and lack of remorse (2) antisocial disorder in joker character developed by childhood trauma and abuse which is caused by his father’s treatments (3) there are three moral messages that can learned from the dark knight movie such as humanity, teamwork, and consideration.